2022
DOI: 10.1158/2326-6066.cir-22-0218
|View full text |Cite
|
Sign up to set email alerts
|

DKK1 Promotes Tumor Immune Evasion and Impedes Anti–PD-1 Treatment by Inducing Immunosuppressive Macrophages in Gastric Cancer

Abstract: Tumor-associated macrophages (TAMs) have key functions in promoting a suppressive tumor immune microenvironment (TIME) and immune evasion, which largely limit treatment effects of immune checkpoint inhibitors (ICIs) in different cancers, including gastric cancer (GC). Dickkopf-1 (DKK1) associates with tumor progression and has been shown to negatively regulate anti-tumor immunity, but the impact of DKK1 on the TIME remains incompletely understood. Here, we found that tumoral DKK1 expression closely associated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…Previous studies have shown that DKK1 promotes malignant phenotypes in hepatocellular carcinoma, including tumor angiogenesis, invasion, and metastasis. It has recently been demonstrated that DKK1 promotes immune escape and impairs anti‐PD‐1 therapeutic efficacy in GC 15 . Therefore, we further explored the effect of DKK1 on the malignant phenotype of AFPGC and found that it promoted AFP expression, as well as proliferation, migration, and EMT of AFPGC.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have shown that DKK1 promotes malignant phenotypes in hepatocellular carcinoma, including tumor angiogenesis, invasion, and metastasis. It has recently been demonstrated that DKK1 promotes immune escape and impairs anti‐PD‐1 therapeutic efficacy in GC 15 . Therefore, we further explored the effect of DKK1 on the malignant phenotype of AFPGC and found that it promoted AFP expression, as well as proliferation, migration, and EMT of AFPGC.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, DKK1 has a more significant diagnostic value than AFP in hepatocellular carcinoma 14 . It has been recently demonstrated that DKK1 promotes immune escape and impairs anti‐PD‐1 therapeutic efficacy in GC 15 . However, there is no literature on the relationship between DKK1 and the malignant phenotype or AFP expression in AFPGC.…”
Section: Introductionmentioning
confidence: 99%
“…In more recent studies, Dkk-1 has also been shown to potently modulate the immunological landscape of the tumor in favor of immune evasion ( 97 ). In this capacity, Dkk-1 has been reported to stimulate the activity of immune suppressive macrophages in gastric cancer ( 98 ), increase numbers of regulatory macrophages and T-cells in cholangiocarcinoma ( 99 ), and Dkk-1 expression is correlated with natural killer T-cell quiescence in prostate cancer ( 100 ). Interestingly, Dkk-1 has been shown to enhance the activity of immune suppressive myeloid derived suppressor cells (MDSCs) by directly targeting cWnt activity, resulting in greater numbers of intratumoral MDSCs that can participate in immune evasion ( 101 ).…”
Section: Discussionmentioning
confidence: 99%
“…We in fact see greater representations of the aforementioned hubs after chemotherapy and after aPD1 in patients that are slow to progress (have more durable responses) compared to those that progress faster. From a clinical perspective it remains unclear whether the optimal strategy is to attempt to restrain the initial formation of anti-immunity hubs with agents that deprive the TME of immunosuppressive signals as has been attempted with neutralizing antibodies to IL-6 54 and DKK1 67 , or to try to directly stimulate the induction of pro-immunity hubs with agonist approaches like STING 68,69 or TLR7/8 70,71 . Towards the later approach, we find that programs for plasmacytoid and conventional dendritic cell subsets were present in hubs that favored slow progression (e.g.…”
Section: Discussionmentioning
confidence: 99%